The reduced activity of PP-1α under redox stress condition is a consequence of GSH-mediated transient disulfide formation. Issue 1 (December 2018) - Singh, Simranjit; Lämmle, Simon; Giese, Heiko; Kämmerer, Susanne; Meyer-Roxlau, Stefanie; Alfar, Ezzaldin; Dihazi, Hassan; Guan, Kaomei; El-Armouche, Ali; Richter, Florian
Abstract Heart failure is the most common cause of morbidity and hospitalization in the western civilization. Protein phosphatases play a key role in the basal cardiac contractility and in the responses to β-adrenergic stimulation with type-1 phosphatase (PP-1) being major contributor. We propose here that formation of transient disulfide bridges in PP-1α might play a leading role in oxidative stress response. First, we established an optimized workflow, the so-called "cross-over-read" search method, for the identification of disulfide-linked species using permutated databases. By applying this method, we demonstrate the formation of unexpected transient disulfides in PP-1α to shelter against over-oxidation. This protection mechanism strongly depends on the fast response in the presence of reduced glutathione. Our work points out that the dimerization of PP-1α involving Cys39 and Cys127 is presumably important for the protection of PP-1α active surface in the absence of a substrate. We finally give insight into the electron transport from the PP-1α catalytic core to the surface. Our data suggest that the formation of transient disulfides might be a general mechanism of proteins to escape from irreversible cysteine oxidation and to prevent their complete inactivation.